Immune-based combinations for the treatment of metastatic renal cell carcinoma: a meta-analysis of randomised clinical trials. (September 2021) - Massari, Francesco; Rizzo, Alessandro; Mollica, Veronica; Rosellini, Matteo; Marchetti, Andrea; Ardizzoni, Andrea; Santoni, Matteo
Abstract: Background: Recent years have witnessed the advent of novel treatment options for metastatic renal cell carcinoma (mRCC), including combination therapies with immune checkpoint inhibitors. Herein, we conducted an up-to-date and comprehensive meta-analysis including recently published data of phase III clinical trials evaluating immune-based combinations in mRCC. Methods: We retrieved all the relevant trials published from 15th June 2008 to 24th February 2021, evaluating immune-based combinations in treatment-naïve mRCC through PubMed/MEDLINE, Cochrane library, and EMBASE; additionally, proceedings of the main international oncological meetings were also searched for relevant abstracts. Outcomes of interest included overall survival (OS), progression-free survival (PFS), complete response (CR) rate, and overall response rate (ORR). Hazard ratios (HRs) and their 95% confidence intervals (CIs) for OS and PFS, and odds ratios (ORs) and 95% CIs for CR rate and ORR, were extracted. Results: Overall, 6 phase III studies involving 5175 treatment-naïve mRCC patients were available for the meta-analysis (immune-based combinations, n = 2576; sunitinib, n = 2597). According to our results, the use of immune-based combinations decreased the risk of death by 26% (HR 0.74, 95% CI 0.67–0.81, P < 0.001); similarly, a PFS benefit was observed (HR 0.68, 95% CI 0.54–0.85, P = 0.001). In addition, immune-based combinations showed better CR rate and ORR, with ORs of 3.04 (95% CI 2.31–3.99, P = 0.001) and 2.53 (95% CI 1.77–3.62, P < 0.03), respectively. Conclusions: The results of our meta-analysis confirm the clinical benefit provided by immunotherapy combinations, with CR rate more than tripled in mRCCs receiving immune-based combinations. Further studies in real-world setting are warranted to validate the findings of our meta-analysis, the most updated to systematically evaluate immune-based combinations in mRCC. Highlights: Immune-based combinations have revolutionised the first-line setting of mRCC. This is a meta-analysis of phase III trials assessing immune-based combo in mRCC. Immunotherapy combo showed superior OS, PFS, CR rate and ORR. Our results confirm the clinical benefit provided by immunotherapy combinations.